Vilniaus daugiabučių gyvenamųjų namų statybos raidos tendencijos nepriklausomybės laikotarpiu - Čaikauskas, Gintaras (Journal of Architecture and Urbanism, 2008)
Residential housing development in vilnius over the period of Lithuanian independence The paper is dedicated to the residential housing development in Vilnius during the years of the Lithuanian independence. Interruption of the natural society development by the aggression of the soviet system has ruined the architectural and building traditions in the city. Economic nationalization and change of property ownership from private to state or public has made a big mess in the land and real estate ownership. On the other hand, many interesting public buildings, built in the soviet period, have lost their actuality and are intended to be sold to private investors. The market economy has money-based urban development rules, so survival of the soviet-period architecture is under a big question too with a great wish of new businessmen to change it into residential areas. New approach to the modern conception of residential architecture development is gradually turning into live reality in independed Lithuania. It will take some time while the new approach to of the architectural image will be turned into an additional price of real estate as an essential value. Article in Lithuanian. Santrauka. Architektūriniu aspektu analizuojamos Vilniaus daugiabučių gyvenamųjų namų statybos raidos tendencijos Nepriklausomybės laikotarpiu, lyginant jas su ikikariniu bei sovietmečio periodais, nagrinėjamos išliekamosios meninės vertės formavimosi prielaidos. Nagrinėjamos naujausių laikų realizacijos, jų specifika ir ypatybės, atskleidžiami esminiai konceptualiai skirtingų sprendimų bruožai. Reikšminiai žodžiai: investicijų modelis, miesto infrastruktūra, juridinė bazė, detalieji planai, teritorijų urbanizavimas, pastatų modernizavimas. First Published Online: 22 May 2013